2020
DOI: 10.3389/fphys.2020.00278
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Activation of Thin Filaments in Striated Muscle

Abstract: In skeletal and cardiac muscles, contraction is triggered by an increase in the intracellular Ca 2+ concentration. During Ca 2+ transients, Ca 2+-binding to troponin C shifts the "on-off" equilibrium of the thin filament state toward the "on" sate, promoting actomyosin interaction. Likewise, recent studies have revealed that the thin filament state is under the influence of temperature; viz., an increase in temperature increases active force production. In this short review, we discuss the effects of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Moreover, studies taking advantage of an in vitro motility assay showed that increasing temperature induces sliding movements of reconstituted thin filaments in the absence of Ca 2+ (pCa 9), above 35°C with human cardiac Tm and bovine cardiac Tn ( Ishii et al, 2019a ) and above 43°C with human cardiac Tm and human cardiac Tn ( Brunet et al, 2012 ). These findings obtained under various experimental conditions are in agreement with the supposition that crossbridge cycling is accelerated by heating in a Ca 2+ -independent manner (see Ishii et al, 2019a , 2020 for details).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, studies taking advantage of an in vitro motility assay showed that increasing temperature induces sliding movements of reconstituted thin filaments in the absence of Ca 2+ (pCa 9), above 35°C with human cardiac Tm and bovine cardiac Tn ( Ishii et al, 2019a ) and above 43°C with human cardiac Tm and human cardiac Tn ( Brunet et al, 2012 ). These findings obtained under various experimental conditions are in agreement with the supposition that crossbridge cycling is accelerated by heating in a Ca 2+ -independent manner (see Ishii et al, 2019a , 2020 for details).…”
Section: Introductionsupporting
confidence: 88%
“…Ambient temperature is an important factor that affects myofibrillar Ca 2+ sensitivity in both skeletal and cardiac muscles (e.g., Mühlrad and Hegyi, 1965 ; Murphy and Hasselbach, 1968 ; Hartshorne et al, 1972 ; Stephenson and Williams, 1981 ; Harrison and Bers, 1989 ). It has been reported that heating elicits myofibrilar force generation in a Ca 2+ -independent manner (for review see Ranatunga, 2018 ; Ishii et al, 2020 ). For example, heating has been shown to increase active force in intact frog sartorius muscle ( Hill, 1970 ) and skinned rabbit psoas fibers ( Ranatunga, 1994 ) in a relaxing solution.…”
Section: Introductionmentioning
confidence: 99%
“…This was probably because the activation of myosin movement by increasing the temperature increased the number of myosins forming crossbridges [ 28 , 29 , 37 , 38 ]. It is considered that the probability of crossbridge formation was also increased because troponin and tropomyosin became less likely to inhibit myosin crossbridge formation due to thermal fluctuation [ 28 , 29 , 37 , 38 ]. In addition, the thermal fluctuation of the actin filament itself may have increased the probability of proximity to the myosin head and increased the probability of crossbridge formation.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-induced contraction without [Ca 2+ ] i increase could be explained from the perspective of Ca 2+ -independent thermal activation of thin filaments (Ishii et al 2020). In an in vitro motility assay, reconstituted cardiac thin filaments slid on myosin in Ca 2+ -free solution when the temperature was increased over ~ 43 °C (Brunet et al 2012).…”
Section: Muscle Contractions Induced By Heat Pulsesmentioning
confidence: 99%